OPTIMIZATION OF PARENTAL ATTENTION ON SOCIAL SCIENCES MAJOR LEARNING OUTCOMES DURING PANDEMIC IN MTs NEGERI GOWA - Marlina, Sitti (Yayasan Education and Social Center, 2022)
The purpose of this study was to determine optimizing parental attention on social sciences primary learning outcomes during the pandemic at MTs Negeri Gowa. I conducted the Odd Semester of 2020/2021 Academic Year research. This research took place in MTs Negeri Gowa. The population of this research is 100 students of class VIII MTs Negeri Gowa, and the sample is as many as 80 students. The research method used is a quantitative approach. The independent variable is parental attention (X), and the dependent variable (Y) is student learning outcomes in social sciences subjects. Data collection techniques include questionnaires, documentation, and interviews. Based on the results of research hypothesis testing, the results of a regression coefficient of 0.081 with a significance value of 0.045<0.045 show that the greater the attention of parents, the higher the learning outcomes. The influence of parental engagement (X) on student achievement (Y) determines by the coefficient , which is 0.045 or 4.5%. It means that parental engagement determines the increase/decrease in student achievement by 4.5%. At the same time, the remaining 96.5% is determined by other changes that also affect student learning outcomes